Pengaruh Kualitas Pelayanan, Kualitas Produk dan Promosi terhadap Kepuasan Konsumen pada Produk “Kopi Dari Hati” di Perumahan Taman Aster Cikarang Barat - Ronaldo Fajar Mardika (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Kopi dari Hati is a famous coffee brand because its franchises can be found in all major cities in Indonesia. Research related to consumer satisfaction is needed. This research is research conducted in the Taman Aster Housing area to look for the influence of service quality, product quality and promotion on consumer satisfaction with the product